Penerapan Prinsip - prinsip Parent Child Interaction Therapy Untuk Menurunkan Sibling Rivalry Pada Remaja - Septhi Karlina Utami; Hendriati Agustani; Langgersari Elsari Novianti (Universitas Islam Indonesia, 2017)
This research was carried out to obtain an intervention program design by using Parent-Child Interaction Therapy (PCIT) principles which could decrease sibling rivalry in adolescent who has younger sibling with intellectual disability.This research involved two pairs of mother and child (adolescent) who were sampled through use of purposive sampling and tried out by using quasi experimental method with A-B-A design. The data were obtained through interviews, observation, and questionnaire. The measurement tools were Sibling Rivalry questionnaire and Dyadic Parent-Child Interaction Coding System III (DPICS-III). There was decline in sibling rivalry and increase in mother’s ability to apply PCIT skills. Meanwhile the qualitative data showed that PCIT skills mastered and applied by the mothers in daily basis parenting made the children to feel respected and could decrease jealousy, anger, and rivalry feeling with their siblings.Keywords: Parent-Child Interaction Therapy (PCIT), Sibling Rivalry, Sibling Relationship, Adolescent,Intellectual Disability.